Christian Missions and Covid-19 in Africa and Latin America: A Case Study of Brazil, Nigeria, and South Africa - Ashe, Muesiri O.; Ojong, Vivian Besem (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Congregational worship among the religious organizations in Africa and Latin America, particularly the rapidly expanding Christian missions, has been of significant consideration in the light of medical recommendations involving social distancing and avoidance of large social gatherings concerning the coronavirus pandemic. This is among recent observations and has attracted more focus following an acute controversy over the role of the Church in Brazil vis-à-vis government policies on the Covid-19 pandemic and the fact that a number of churches in Nigeria were allegedly initially reluctant to respond to the government lockdown declaration and the resultant ban on congregational worship. Simultaneously, the agenda of financial and material assistance to the poor by the large Christian denominations in South Africa as one means of sustaining the lockdown rather attracted criticism, as they were unable to sustain the project. Furthermore, the role of religious bodies came to the fore as global surveys demonstrated that, on average, the masses in these two continents are among the most religiously observant people in the world. As we shall see in the concluding section, this is the major consideration of Idayat Hassan, Director of the Abuja-based Centre for Democracy and Development, in his assessment of the African context.